2018
DOI: 10.1177/0023677218766391
|View full text |Cite
|
Sign up to set email alerts
|

Pigs are useful for the molecular study of bone inflammation and regeneration in humans

Abstract: Pigs are used with increased frequency to model different kinds of orthopedic surgical conditions. In order to show the full potential of porcine models in orthopedic research, it is therefore required to examine the expression of bone regulatory genes in pigs affected by orthopedic surgery and compare it to the expression in humans and mice as mice, are one of the most applied animal species in orthopedics today. In the present study, the local molecular response to drilling of a tibial implant cavity, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Furthermore, bone remodelling and cortical bone mineralization rates in pigs and humans are similar [43,44,46]. Finally, a recent study on the porcine IAO model inoculated with saline demonstrated that the local expression pattern of inflammatory and bone regulatory genes in bone tissue exposed to surgery was similar to that reported in human studies [10].…”
Section: Pathological Remarkssupporting
confidence: 61%
See 2 more Smart Citations
“…Furthermore, bone remodelling and cortical bone mineralization rates in pigs and humans are similar [43,44,46]. Finally, a recent study on the porcine IAO model inoculated with saline demonstrated that the local expression pattern of inflammatory and bone regulatory genes in bone tissue exposed to surgery was similar to that reported in human studies [10].…”
Section: Pathological Remarkssupporting
confidence: 61%
“…In saline-inoculated animals, the surgical inoculation procedure per se resulted in thermal bone necrosis and debris around the implant cavity (Fig. 12B; II, III) [10]. In addition, a small amount of inflammatory cellular infiltration occurred.…”
Section: Post-mortem Quantification Of Bone Infection -mentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of general anaesthesia is known to cause physiological alterations that may have affected the local tissue metabolism. Although pigs have been shown to resemble humans in terms of physiology, anatomy and bone inflammation and regeneration (30)(31)(32)(33), the porcine intervertebral disc and vertebral cancellous bone differ from that of humans in several ways (15).…”
Section: Discussionmentioning
confidence: 99%
“…While nonhuman primates are the most representative model of the human immune system ( Wagar et al, 2018 ), pigs and sheep are normally used to model bone repair since their bone anatomy, mineral composition, regeneration capacity and biomechanical properties are relatively similar to human’s ( Sparks et al, 2020 ). Moreover, compared to mice, their immune system is closer to the human one ( Lüthje et al, 2018 ). As a consequence, pigs and sheep are the first choices as large animal models of the inflammatory response in bone fracture healing.…”
Section: Experimental Validation Of In Silico Modelsmentioning
confidence: 99%